From Reformist Thought to Institutional Transformation: KH Ahmad Dahlan and the Making of Muhammadiyah - Apris Yaman; Desi Asmaret; Julhadi; Syaifullah (Suria Academic Press, 2026)
The emergence of Muhammadiyah represents a pivotal milestone in the history of Islamic reform in Indonesia, closely linked to the pioneering thought of KH Ahmad Dahlan. Nevertheless, previous studies have predominantly focused on Muhammadiyah as an organization or Ahmad Dahlan as its founder, leaving limited attention to the reconstruction of his ideas as the conceptual foundation of the Muhammadiyah reform movement. This study aims to analyze the pioneering thought of KH Ahmad Dahlan in shaping the Muhammadiyah reform movement and to explain how his ideas were institutionalized into a sustainable socio-religious movement. The research employs a qualitative conceptual approach based on an extensive literature review of reputable journal articles, academic books, and relevant documents. Data were analyzed using qualitative content analysis supported by the perspectives of Islamic Modernism, Social Movement Theory, and Institutional Theory. The findings reveal that Ahmad Dahlan's reform paradigm consists of five interconnected dimensions: purification of Islamic creed, revitalization of ijtihad, integration of Islamic and modern education, Al-Ma'un-based social theology, and organizational modernization. These dimensions enabled Muhammadiyah to institutionalize Islamic values through education, healthcare, philanthropy, and community empowerment, ensuring its sustainability as a reform movement. This study contributes to the literature by providing a conceptual reconstruction of the relationship between Islamic reformist thought, institutional development, and the sustainability of Muhammadiyah. The findings also offer practical insights for strengthening moderate Islamic movements and promoting adaptive Islamic education in addressing contemporary social and technological challenges.